Philip Rieff’s typology of culture and its applicability to the literary hybridization of the theological ideas of humanity and spiritual progress (a Bulgarian case study) - Grażyna Szwat-Gyłybowa (Slavia Meridionalis, 2016)
Philip Rieff’s typology of culture and its applicability to the literary hybridization of the theological ideas of humanity and spiritual progress (a Bulgarian case study)